PdMATE16 and PdMATE35 are essential for the accumulation of multiple flavonoids in tree peonies - Yuan, Meng; Wei, Xinrui; Peng, Fucheng; Wang, Qun; Zhou, Lin; Wang, Yan (Frontiers in Plant Science, 2025)
As a plant with both medicinal and edible uses, peonies are not only valued for their ornamental qualities, but also for the high economic value of the flavonoids found in their petals. However, the regulatory mechanisms governing flower color and flavonoid transport remain unclear. The multidrug and toxic compound extrusion (MATE) family of proteins are important transport protein involved in the transport of a variety of secondary metabolites in plants. Based on transcriptomic data, this study identified 37 MATE genes from the transcriptomic data of Paeonia delavayi var. lutea. Molecular docking and site-directed mutagenesis results predict that PdMATE16 and PdMATE35 can bind multiple pigments. Overexpression and virus-induced gene silencing (VIGS) experiments further confirmed that PdMATE16 and PdMATE35 could transport a variety of flavonoid compounds, including flavone glycosides, flavonol glycosides, chalcone glycosides and anthocyanin glycosides. These substances not only give peonies their yellow color, but are also the main active ingredients in medicinal applications. In addition, several transcription factors that may be involved in regulating MATE gene expression were screened. Our research confirms the key role of PdMATE16 and PdMATE35 in flavonoid transport in peonies, clarifies the regulatory mechanism underlying the transport processes involved in peony coloration, and may thus contribute to the improvement of ornamental and medicinal plants.